2022
DOI: 10.1002/pssa.202200200
|View full text |Cite
|
Sign up to set email alerts
|

SeO2 Microwires Designed as Low‐Temperature Abrupt Microelectronic Switches, Negative Resistance, and Negative Dielectric Constant Sources

Abstract: Herein, the structural, morphological, compositional, and electrical properties of SeO2 microwires are studied and analyzed. Microwires of SeO2 with dimensions of 460 ×  30 × 30  ( μ m )   3 are electrically characterized in the temperature range of 17–300 K. SeO2 microwires are observed exhibiting nanocrystalline structures relating to a tetragonal phase. The microwires contained excess oxygen leading to some Se vacancies. The current–voltage (I–V) characteristics of the microwires displayed temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Earlier studies have also shown that Yb/SiO 2 interfaces conduct current by tunneling process [14]. In addition SeO 2 in thin film and microwire form [38] are also observed to exhibit charge tunneling due to the charge instabilities [13]. The excess charges carriers generated from the impact ionization transferring to the low mobility states, can leads to a strong space-charge instability [13].…”
Section: Resultsmentioning
confidence: 91%
“…Earlier studies have also shown that Yb/SiO 2 interfaces conduct current by tunneling process [14]. In addition SeO 2 in thin film and microwire form [38] are also observed to exhibit charge tunneling due to the charge instabilities [13]. The excess charges carriers generated from the impact ionization transferring to the low mobility states, can leads to a strong space-charge instability [13].…”
Section: Resultsmentioning
confidence: 91%